2020
DOI: 10.1029/2020gh000249
|View full text |Cite
|
Sign up to set email alerts
|

Community Citizen Science for Risk Management of a Spontaneously Combusting Coal‐Mine Waste Heap in Ban Chaung, Dawei District, Myanmar

Abstract: Since 2015, a large heap of improperly disposed coalmine waste in Ban Chaung, Dawei district, Myanmar, has repeatedly spontaneously combusted, affecting an indigenous community. Recently, the regional Myanmar government has compelled the mine to properly manage the mine waste heap, but there is no opportunity for affected villagers to participate. This study empowers the affected villagers to make risk management decisions via a community citizen science approach. First, field investigations were performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…▪ In Myanmar, for example, previous efforts by villagers in the Ban Chaung, Dawei District to collect data on the burning waste heap were interpreted as clear evidence of past poor waste management and fire suppression by the mining company (Phenrat 2020). New data allowed the community to influence enforcement decisions, elevate democratic capacity, and empower marginalized individuals and communities to advocate for scientifically appropriate mitigation options (Phenrat 2020).…”
Section: Figure 1 | Monitoring Approach Used In Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…▪ In Myanmar, for example, previous efforts by villagers in the Ban Chaung, Dawei District to collect data on the burning waste heap were interpreted as clear evidence of past poor waste management and fire suppression by the mining company (Phenrat 2020). New data allowed the community to influence enforcement decisions, elevate democratic capacity, and empower marginalized individuals and communities to advocate for scientifically appropriate mitigation options (Phenrat 2020).…”
Section: Figure 1 | Monitoring Approach Used In Case Studiesmentioning
confidence: 99%
“…▪ In Myanmar, for example, previous efforts by villagers in the Ban Chaung, Dawei District to collect data on the burning waste heap were interpreted as clear evidence of past poor waste management and fire suppression by the mining company (Phenrat 2020). New data allowed the community to influence enforcement decisions, elevate democratic capacity, and empower marginalized individuals and communities to advocate for scientifically appropriate mitigation options (Phenrat 2020). In San Diego, California, the work of the Environmental Health Coalition (EHC) and its partnership substantially impacted air quality regulatory action, including passage of an amortization ordinance and a law to limit the operation of a truck-driving school adjacent to the local elementary school, as well as the securing of funds for a feasibility study for an industrial park outside the city limits (Minkler et al 2010).…”
Section: Figure 1 | Monitoring Approach Used In Case Studiesmentioning
confidence: 99%
“…It is found that the emergency stations covering all mining areas are set up underground to provide medical first aid and transportation of injured in the shortest time [10]. In addition, it is significant for rescue to improve the existing refuge chamber and strengthen the escape simulation training [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gangue, which is a waste product of global coal and carbon energy industry, has the properties of easy acidification with high sulfur content [ 1 ]. The stock of coal gangue in China has reached the level of 1 billion and is increasing at a rate of 200 million per year [ 2 ].…”
Section: Introductionmentioning
confidence: 99%